Mapping Geographic Variation in Infant Mortality and Related Black–White Disparities in the US. Issue 5 (September 2016) - Rossen, Lauren M.; Khan, Diba; Schoendorf, Kenneth C.
Abstract : Background: In the US, black infants remain more than twice as likely as white infants to die in the first year of life. Previous studies of geographic variation in infant mortality disparities have been limited to large metropolitan areas where stable estimates of infant mortality rates by race can be determined, leaving much of the US unexplored. Methods: The objective of this analysis was to describe geographic variation in county-level racial disparities in infant mortality rates across the 48 contiguous US states and District of Columbia using national linked birth and infant death period files (2004–2011). We implemented Bayesian shared component models in OpenBUGS, borrowing strength across both spatial units and racial groups. We mapped posterior estimates of mortality rates for black and white infants as well as relative and absolute disparities. Results: Black infants had higher infant mortality rates than white infants in all counties, but there was geographic variation in the magnitude of both relative and absolute disparities. The mean difference between black and white rates was 5.9 per 1, 000 (median: 5.8, interquartile range: 5.2 to 6.6 per 1, 000), while those for black infants were 2.2 times higher than for white infants (median: 2.1, interquartile range: 1.9–2.3). One quarter of the county-level variation in rates for black infants was shared with white infants. Conclusions: Examining county-level variation in infant mortality rates among black and white infants and related racial disparities may inform efforts to redress inequities and reduce the burden of infant mortality in the US. Abstract : Supplemental Digital Content is available in the text.